Penerapan Manajemen Peserta Didik Melalui Pemberian Reward Di Sekolah Dasar Kota Makassar - Herlina Triyanti; Andi Nurochmah; Irmawati Irmawati (Universitas Negeri Makassar, 2022)
The purpose of this study was to determine the application of student management in giving rewards at MakassarCityElementarySchool. Thisstudyusedaqualitativeapproachwithadescriptivetype,datacollectionthroughinterviews,observation,anddocumentation.Thesubjectsofthestudywerefour teachers and eight students. The results showed that student management in giving rewards was: 1) The results showed that elementary school students in Makassar City had rewards, interest in learning, readiness to learn, learning attention, learning achievement, learning perseverance; and tenacious in the face of difficulties, namely experiencing improvements in the learning process, 2) Supporting factors for rewarding are supported from teachers, the responses shown by students during and after receiving rewards, and students' desire to achieve other achievements. 3) The inhibiting factors in the implementation of rewarding are a large number of students, the preparation of equipment in giving rewards such as achievement stars, achievement boards, and also award charters), and the limitations of teachers in making observations so that they are not observant. There are also no guidelines used in giving rewards in the form of award certificates to students.